POTENSI AFRODISIAK KANDUNGAN AKTIF BUAH CABE JAWA (Piper retrofractum Vahl) PADA TIKUS JANTAN GALUR WISTAR - Siti Muslichah (JURNAL AGROTEKNOLOGI, 2011)
Java long pepper (Piper retrofractum Vahl) is one of the Indonesian original plants having aphrodisiac activity. This study was aimed to isolate piperine and to evaluate aphrodisiac potency of piperine and piperine-free insoluble n-hexane fraction from ethanolic extract of P. retrofractum. Twenty five male rats were randomized into 5 groups. Oral repeated administration once a day for 27 days were given to andriol group (0.72 mg/day), CMC-Na 1%, piperine (1.6 mg/kg body weight), piperine-free insoluble n-hexane fraction (2.1 mg/kg body weight), insoluble n-hexane fraction (31.72 mg/kg body weight). Rat’s sexual behavior including sexual introduction and climbing were observed in day 0, 1, 3, 5, 7, 11, 15, 19, 23, and 27. Normal and homogenous data were analyzed statistically with one-way ANOVA, followed by LSD test. The result showed that the administration of andriol, piperine, piperine-free insoluble n-hexane fraction, and total insoluble n-hexane fraction has a significant increase in the frequency of introduction, compared to the group of CMC-Na 1% (p<0.05). There was also a significant increase of piperine and piperine-free insoluble n-hexane fraction in the frequency of climbing (p<0.05).Keywords: Piper retrofractum Vahl, sexual behavior, piperine, aphrodisiac